A Novel MFS Transporter Gene ChMfs1 Is Important for Hyphal Morphology, Conidiation, and Pathogenicity in Colletotrichum higginsianum - Liu, Liping; Yan, Yaqin; Huang, Junbin; Hsiang, Tom; Wei, Yangdou; Li, Yu; Gao, Jie; Zheng, Lu (Frontiers in Microbiology, 2017)
Colletotrichum higginsianum is a widely distributed fungus attacking many cruciferous species. To investigate pathogenic mechanisms of the pathogen on the host Arabidopsis thaliana, we screened and obtained a virulence-deficient mutant Ch-1-T513 in a T-DNA insertion mutant library of C. higginsianum. The mutant Ch-1-T513 produced yellow colony centers with distorted multi-branching hyphal tips as well as producing few conidia. Heavily swollen hyphae in the mutant could be observed, and intra-hyphal hyphae were found to be formed in the balloon-shaped hyphae. The mutant failed to produce lesions on 12-day-old Arabidopsis seedlings, and invasive hyphae did not differentiate into large primary and thin secondary hyphae after appressorial formation on Arabidopsis leaves, but formed abundant bulbous hyphae in epidermal cells. Southern blot analysis showed Ch-1-T513 had double-site T-DNA integrations. The mutant had insertions upstream of genes for a major facilitator superfamily (MFS) transporter, ChMfs1 and an aldo/keto reductase, ChAkr. Complementation experiments by transforming genomic sequences from a wild-type strain into the insertion mutant demonstrated that ChMfs1 is involved in the Ch-1-T513 phenotype. The complementation strain C-ChMfs1-1 exhibited normal hyphal morphology, conidiation and pathogenicity identical to the wild-type. The results demonstrate that ChMfs1 is involved in intra-hyphal hyphae production, conidiation and pathogenicity in C. higginsianum. To our knowlege, this is the first report of a MFS transporter gene in a phytopathogenic fungus associated with intra-hyphal hyphae formation, playing a key role in infection of its plant host.